A novel rapid alloy development method towards powder bed additive manufacturing, demonstrated for binary Al-Ti, -Zr and -Nb alloys. (1st December 2021) - Leijon, Freddy; Wachter, Sebastian; Fu, Zongwen; Körner, Carolin; Skjervold, Svein; Moverare, Johan
Graphical abstract: Highlights: A novel high through put method was developed for PBF material development. Long compositional gradients with PBF mimicked microstructure was produced. Shifts in material properties could be followed with high compositional resolution. Abstract: Powder bed fusion (PBF) methods offer the best material properties among metal additive manufacturing (AM) processes. Yet, alloy development for PBF is only at its infancy and has a great untapped potential. This originates from the high solidification rate within the melt pool and to exploit the full potential of materials produced by PBF methods, a diligent work lies ahead. This paper presents a high-throughput method to rapidly screen large compositional alloy intervals experimentally for their PBF feasibility, which can drastically reduce the time needed for alloy development and provide valuable data for modelling. Our method consists of two steps; co-sputtering and electron beam re-melting. First step produces an alloy gradient film on a sheet substrate. The film is then re-molted to produce a PBF mimicked microstructure. The method is successfully demonstrated on binary systems; Al -Ti, -Zr and -Nb and produced gradients in compositional ranges of 3–50 wt%Ti, 1–15 wt%Zr and 2–15 wt%Nb over a length of 200 mm. From the produced materials, the alloying efficiency could be investigated and determined regarding hardness and grain refinement. Zr shows the highest strength contribution per at% and the best grain refinement at low levels. However, at higher levels grain refinement efficiency decreases for Zr.